Inducing models of human control skills - Rui Camacho (1998)
A new model of human control skills is proposed and empiri-cally evaluated. It is called the incremental correction model and is more adequate for reverse engineering human control skills than any other previously proposed models. The experimental results show a considerable increase in robustness of the controllers that use the new model.The new model also attenuates the problem of unbalanced classes, noticed already in previous experiments. By means of Parameterised Decision Trees, propositional learners are still usable within the new model's framework.